Avaliação de manifestações patológicas com aplicação do método FMECA – estudo de caso. - Maia, Évelyn Barbara de Melo (Universidade Federal Rural do Semi-Árido, 2019)
Buildings have a life cycle that must be guaranteed through the correct use of materials and quality of workmanship, and can be extended by adopting a periodic maintenance plan. If some of these items fail, it’s life cycle is reduced through the development of pathological manifestations that can trigger aesthetic and structural problems. Understanding the different manifestations is indispensable for a correct analysis of the problem and the adoption of appropriate treatments. For this, different methods of analysis have been created or modified to assist in pathological investigations of construction. Thus, this paper aims to perform an analysis of the main pathological manifestations found in the City council of Mossoró, using for this purpose a methodological adaptation of the administrative tool entitled as FMECA (Failure, Mode, Effects and Criticality Analysis). A visual inspection and inspection were also performed accompanied by non-destructive tests to assist and support the diagnosis. From the application of FMECA it was possible to design an evaluation form identifying the degree of risk priority of each floor of the building. Most of the pathological manifestations identified in the City Council are related to humidity. In conclusion, it was clear that the method allowed us to indicate which pavement needs the most attention and what effect led to the cause of the problem
Monografia
Keywords: Construção civil; Patologia nas edificações; Durabilidade; Grau de risco; Construction; Pathology in buildings; Durability; Degree of risk; ENGENHARIAS::ENGENHARIA CIVIL